ANALISIS PENGARUH CAPITAL ADEQUANCY RATIO, LOAN TO DEPOSIT RATIO, DAN NON PERFORMING LOAN TERHADAP JUMLAH KREDIT YANG DISALURKAN PADA PT BANK SUMUT PERIODE 2014-2017 - Pakpahan, Benhur (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2018)
The research objective was to determine the effect of Capital Adequacy Ratio, Loan to Deposit Ratio, and Non-Performing Loans on the amount of credit channeled to PT Bank Sumut Medan for the period 2014-2017. The data used is secondary data that is obtained by documentation technique. Data processing by using Multiple Regression Analysis. The results showed that simultaneously the variable Capital Adequacy Ratio, Loan to Deposit Ratio, and Non-Performing Loan had a negative and significant effect on the amount of credit channeled to PT Bank Sumut for the 2015-2017 period.